A delivery model for embedding functional skills on vocational courses in offender learning. Issue 3 (30th September 2014) - Naphray, Sunil
Abstract : Purpose: – The purpose of this paper is to develop a delivery model for embedding Functional Skills in a prison environment, i.e. HMP Oakwood, to promote Functional Skills (FS) on vocational courses, i.e. Maths and Plumbing at Level 1, establish a research culture in a brand new organisation and raise standards in teaching, learning and outcomes. Design/methodology/approach: – The design/methodology of this research included the implementation of a qualitative approach based on classroom research, a focus group with seven students on the Level 1 Plumbing course, joint Practice Development meetings with FS and vocational staff, the development of key principles for creating an embedded model for vocational courses, the creation of lesson plan/bespoke resource developments, lesson observations of the new model followed by teacher and learner evaluation, a practical task (fitting a bathroom suite) undertaken by learners, initial maths exercises drawn from practical task which were vocationally relevant, associations made with real jobs and work, use of IT/video for added interest, highlighting of transferable skills and users undertook dedicated functional maths exercises. Findings: – A delivery model/logical sequence was agreed that worked for the teacher and learners – practical task/contextualised maths/transferable skills focus/situated maths. Targeted questions generated interest – will a litre of bath water hold if you use four in joists? The study allowed learners to reflect on maths elements from the practical task. The delivery model is implemented by vocational, not FS tutors. IT/video was used to introduce further maths for transferability to other related plumbing areas, i.e. fitting an outside garage tap. Constant links with use of maths for real job activity need to be made/reinforce relevance. Good tutor subject knowledge in maths is strongly recommended. Learners are ready to do dedicated/situated maths once they have built up their confidence. Research limitations/implications: – This delivery model can be used across all other vocational courses at HMP Oakwood, i.e. bricklaying, multi-skills, painting and decorating, site carpentry, horticulture, industrial cleaning, catering, horticulture, etc. A framework/pedagogical guide can be developed for vocational tutors to implement this delivery model in their own subject areas as a basis for continued research. Bespoke CPD sessions for vocational staff can be run to share good practice in session plans and resources relevant to the delivery model. Peer observations can be arranged across the vocational department and the impact of the model on lesson observation grades and success rates can be analysed. Practical implications: – Practical implications can include the development of a two-year Learning and Skills Research Strategy with a focus on embedded pedagogy. A senior team leader in FS can become the research lead for the Education Department, and an extensive embedded learning audit across 35 courses can be undertaken by July 2013. Social implications: – Further pedagogical research into embedded learning across the whole department including employability/PSD/IT/business courses can be conducted. Originality/value: – This study offers a simple, practical and ready to use delivery model which will help particularly non-specialist FS maths and English tutors working in vocational areas (i.e. construction, catering, etc.) to embed the teaching of maths and English in their subject areas.